(untitled) (PJDOL, 2023)
An e-learner is more at risk of being demotivated because of limited/no face-to-face interaction with his/her instructor and class fellows. The purpose of this research study was to analyze the status of attention, relevance, confidence and satisfaction of students while studying in an e-learning system.